Komposisi Jenis Ikan dan Udang yang Tertangkap pada Periode Musim Penghujan - Pane, Lindon Robinson; Merly, Sendy Lely; Kamur, Hengki K (Universitas Musamus, Merauke, Papua, 2023)
The wealth of fisheries resources of Merauke Regency is indeed very abundant. This is evidenced by the location of the fishing ground for fishermen who only catch from the beach, one of which is located in Payum Beach. This study aims to determine the composition of fish and shrimp catches during the wet season. Drift gillnet was used as a fishing gear during this study to collect the data. A Total of 13 species were captured, such as Mugil dussumieri and Megalops cyprinoides were the most dominant species during this period. However, based on the number, Penaeid shrimp such as Penaeus sp. and Penaeus semisulcatus are found to be very abundant during the wet season.